A consensus on the use of daylight photodynamic therapy in the UK. (19th May 2017) - Ibbotson, Sally; Stones, Robin; Bowling, Jonathan; Campbell, Sandra; Kownacki, Stephen; Sivaramakrishnan, Muthu; Valentine, Ronan; Morton, Colin A.
Abstract: Background: Actinic keratoses (AKs) are a consequence of chronic exposure to ultraviolet radiation. Treatment of chronically photo-damaged skin and AKs is driven by risk of progression to squamous cell carcinoma, as well as for symptomatic relief. Conventional photodynamic therapy (c-PDT) is indicated when AKs are multiple or confluent and if patients respond poorly or are unable to tolerate other therapies. c-PDT is limited by the field size that can be treated in single sessions and can cause significant discomfort. Objective: Recent studies investigated daylight illumination to activate protoporphyrin IX and daylight-PDT (d-PDT) is now licensed in the UK for face and scalp AKs. A group of experts met to discuss application of d-PDT with methyl aminolevulinate (MAL) and develop a UK consensus statement, specific to UK weather conditions. Methods: The UK consensus recommendations were reached among eight experts, who reviewed recent studies on d-PDT, assessed UK meteorological data and discussed personal experiences of d-PDT for AKs. Results: Recommendations from these discussions provide guidance on d-PDT use, specifically regarding patient selection, therapeutic indications, when to treat, skin preparation, MAL application and daylight exposure for patients with AKs. Conclusions: This UK expert consensus provides practical guidance for UK application of d-PDT.